2018
DOI: 10.1155/2018/2107059
|View full text |Cite
|
Sign up to set email alerts
|

Open Fracture of the Acromion: An Isolated Injury with Oblique-Type Fracture

Abstract: Open acromial fractures are a rare set of fractures. We report a case of Gustilo IIIA open acromial fracture (14A2 as per OTA scapular fracture classification) that was isolated from any other injury. Our patient had a good recovery and showed excellent clinical outcome after irrigation and screw fixation of the acromial fracture. We also reviewed the literature for other cases of open acromial fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“… 13 27 31 32) Acromion open fractures require immediate surgery, not just to seal the soft tissue but also to do additional open reduction and internal fixation. 33 34) Additionally, Baur et al suggested operating on all displaced fractures 35) where anatomic restoration may stop muscle dysfunction and scapular dyskinesia, especially in fractures with reduced subacromial space. 36) …”
Section: Fractures Of the Acromionmentioning
confidence: 99%
“… 13 27 31 32) Acromion open fractures require immediate surgery, not just to seal the soft tissue but also to do additional open reduction and internal fixation. 33 34) Additionally, Baur et al suggested operating on all displaced fractures 35) where anatomic restoration may stop muscle dysfunction and scapular dyskinesia, especially in fractures with reduced subacromial space. 36) …”
Section: Fractures Of the Acromionmentioning
confidence: 99%
“…Scapular fractures comprise <1% of all fractures with acromion fractures being only 8–9% of these [ 1 , 2 , 3 ]. Open fractures of acromion are usually seen in direct trauma with sharp object based on the all the case reports available on this topic [ 4 , 5 ]. These often occur in conjugation with other injuries to the shoulder girdle [ 6 ].…”
Section: Introductionmentioning
confidence: 99%